Pneumomediastinum, Pneumopericardium, and Epidural Pneumatosis following Adenotonsillectomy: A Very Rare Complication - Feride Fatma Görgülü; Ayşe Selcan Koç; Orhan Görgülü (Case Reports in Otolaryngology)
Adenotonsillectomy is a common surgical otolaryngology procedure that is associated with several complications, including hemorrhage, odynophagia, damage to teeth, taste disorders, atlantoaxial subluxation, lingual edema, infection, and injury of the carotid artery. Pneumomediastinum, pneumopericardium, and epidural pneumatosis are an extremely unusual condition in children with adenotonsillectomy. Treatment should be conservative in the majority of cases and based on benign self-limiting course of these diseases; early recognition can prevent further complications. The combination of pneumomediastinum with epidural pneumatosis, pneumopericardium, retropharyngeal-prevertebral pneumatosis, axillar-perihumeral pneumatosis, and subcutaneous emphysema is also a very rare condition. We present a unique case with the radiological findings of air in all of these areas in a 6-year-old male child with adenotonsillectomy. The case was unusual in that the patient developed this complication 3 hours later after adenotonsillectomy with severe vomitting. The possible mechanism, the algorithm of treatment, and precautions in such cases will be discussed.